Evaluation of the endocrine disrupting potential of Di-isodecyl phthalate - I.A. Lea; D. Feifarek; A. Mihalchik; M. Heintz; L. Haws; H. Nyambego; K. Goyak; C. Palermo; S.J. Borghoff (Current Research in Toxicology)
Low molecular weight ortho-phthalates have been implicated in perturbing androgen pathways when administered during the masculinization programming window. Di-isodecyl phthalate (DIDP) is a high molecular weight phthalate and as a high production volume chemical, its ability to disrupt endocrine pathways is important to understand its potential hazard. Both DIDP (and its metabolites) were evaluated to determine the potential to perturb endocrine pathways through a weight of evidence (WoE) assessment in accordance with the European Chemicals Agency (ECHA)/European Food Safety Authority (EFSA) Endocrine Disruptor Guidance (2018). A literature review was performed of toxicological data for DIDP related to estrogen, androgen, thyroid, or steroidogenesis pathways. Literature searches returned 41 relevant articles from which data were extracted and assessed in conjunction with data from 105 high-throughput assays. Because some of the in vitro assays lack metabolic capabilities, an in silico assessment of estrogen (E), androgen (A), thyroid (T) or steroidogenesis (S) activity was conducted. Based on the available evidence for the T pathway, DIDP did not elicit adverse thyroid outcomes in vivo. When considering the T mechanistic data, there was evidence that DIDP induced the liver pregnane X receptor (PXR) and some indication that DIDP increased iodide uptake in the thyroid. As there were no studies evaluating thyroid hormone levels in vivo, a data gap was identified because per the ECHA/EFSA guidance, the lack of this information prevents drawing a conclusion on the T pathway. However, the E, A and S pathways were sufficiently assessed to conclude a limited or lack of E, A or S related apical outcomes in in vivo studies; there was also a lack of endocrine activity in in vitro or in vivo mechanistic studies. These results suggest that DIDP does not meet the ECHA/EFSA criteria for an endocrine disruptor, therefore DIDP is unlikely to disrupt the androgen pathway during development.